Cavity-length optimization for high energy pulse generation in a long cavity passively mode-locked all-fiber ring laser - Shum, Perry Ping (2013)
In order to achieve higher pulse energy in a passively mode-locked fiber ring laser, a long cavity length is commonly implemented. However, a long cavity operating in the anomalous dispersion regime also leads to pulse broadening, which reduces the average pulse power. In this paper, the trade-off between cavity length and average pulse power is investigated with the aim of optimizing the cavity length to achieve maximum pulse energy. Numerical simulation results, presented here, indicate that there exists an optimum cavity length for which the pulse energy is maximum and the optimum length shifts as the pump power changes. The simulation results for a pump power of 500 mW are verified by measurements carried out on a long cavity nonlinear polarization rotation mode-locked all-fiber ring laser operating in the anomalous dispersion regime. With a repetition rate of 266 kHz for the dissipative solitons, we achieve a pulse energy of 139.1 nJ for a cavity length of 700 m. Higher pulse energy can be expected by using a pump laser diode with higher pump power.